Модернізація законодавства про національні меншини в Україні - Вітман, Костянтин Миколайович; Витман, Константин Николаевич; Vitman, Konstantin (My University, 2013)
The main tendencies of the modernization of national minorities' law in Ukraine are studied. The project of the Act on National Minorities in Ukraine and the Identity Right is analyzed for the purpose of correspondence to ethnopolitical safety foundations and international standards relating to the protection of national minorities' rights.
Вітман К. М. Модернізація законодавства про національні меншини в Україні / К. М. Вітман // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 166-174.
Keywords: національно-культурна автономія; національні меншини; етнонаціональна політика; национально-культурная автономия; национальные меньшинства; этнонациональная политика; national cultural autonomy; national minorities; ethnonational politics